Refractory Chronic Diffuse Granular Myringitis with Medial Meatal Stenosis - Siew Wei Ling; Chee Chean Lim; Mohamad Fuad Shah Bin Mohd Damanhuri Shah; Philip Rajan Devesahayam (Journal of International Advanced Otology)
Granular myringitis is a chronic inflammatory condition of the tympanic membrane that does not involve the middle ear. Various treatment modalities have been proposed for the treatment of granular myringitis, but there is no standard treatment regime. A 60-year-old woman had left persistent ear discharge for 4 months. Examination revealed diffuse granulation tissue, forming a pseudomembrane at the medial aspect of the ear canal and obstructing the tympanic membrane. An audiogram revealed mild-to-moderate left-sided conductive hearing loss. She was treated with multiple courses of ear drop antibiotics but had no improvement. The decision for surgical intervention was driven by the presence of a grade IV medial meatal stenosis, the potential risks associated with prolonged medical management, the distressing impact on the patient’s life, and a shared decision-making process. A combined transcanal and postauricular endoscopic approach whereby excision of the granulation tissue, canalplasty, and myringoplasty were performed. She exhibited complete symptom resolution and reported an improved quality of life. This approach yielded successful symptom resolution, highlighting its potential in managing refractory chronic granular myringitis. We aimed to carefully weigh the risks of surgery against its potential benefits in a refractory chronic case, acknowledging the inherent risks and disadvantages of surgical interventions. Further studies are warranted to evaluate the long-term outcomes and benefits of this approach.